2023
DOI: 10.3389/fimmu.2023.1181697
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative single-cell RNA sequencing and metabolomics decipher the imbalanced lipid-metabolism in maladaptive immune responses during sepsis

Abstract: BackgroundTo identify differentially expressed lipid metabolism-related genes (DE-LMRGs) responsible for immune dysfunction in sepsis.MethodsThe lipid metabolism-related hub genes were screened using machine learning algorithms, and the immune cell infiltration of these hub genes were assessed by CIBERSORT and Single-sample GSEA. Next, the immune function of these hub genes at the single-cell level were validated by comparing multiregional immune landscapes between septic patients (SP) and healthy control (HC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The single-sample Gene Set Enrichment Analysis (ssGSEA) method was used to assess the level of immune cell infiltration in sepsis samples across different MAAGs subgroups, utilizing the "GSVA" R package 10 . ssGSEA requires predefined gene sets that are indicative of specific immune cell types.…”
Section: Methodsmentioning
confidence: 99%
“…The single-sample Gene Set Enrichment Analysis (ssGSEA) method was used to assess the level of immune cell infiltration in sepsis samples across different MAAGs subgroups, utilizing the "GSVA" R package 10 . ssGSEA requires predefined gene sets that are indicative of specific immune cell types.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids are an essential part of a cell’s biomolecular pool and play important roles in a myriad of complex biological processes with biophysical, energy storage, and signaling functions (reviewed in ). Recent studies demonstrate that analyzing lipids at the single-cell level not only reveals significant variation in lipid profiles between different cells but is also capable of observing putative response to stimuli, such as treatment with drugs or exogenous fatty acids. Cancer cells are highly heterogeneous and very diverse in their phenotype which makes them hard to extinguish, but the analysis of single cells and the characterization of the heterogeneity could provide new treatment strategies . Pancreatic ductal adenocarcinoma is the most common pancreatic cancer with the poorest prognosis for pancreatic diseases .…”
Section: Introductionmentioning
confidence: 99%
“… 3 The heart was the organ most commonly implicated in hemorrhagic shock, and once cardiac dysfunction happened, the prognosis further deteriorated. 4 , 5 Previous studies reported that the mechanisms of myocardial injury in hemorrhagic shock were mainly related to inflammation, autonomic dysfunction, and apoptosis. 6 , 7 However, the therapeutic efficacy targeted to these mechanisms was not ideal.…”
Section: Introductionmentioning
confidence: 99%